Tinjauan Motivasi Kerja dan Tingkat Pendidikan pada Kinerja Penyuluh Keluarga Berencana - Harries Madiistriyatno; Ernawati Ernawati (Syntax Idea, 2021)
This study aims to determine the effect of Work Motivation and Education Level on the Performance of Family Planning Instructors. The sampling technique used total sampling (n = 44), and the data analysis technique used Correlation and Regression with SPSS version 22. The results showed that Work Motivation had a positive and significant effect on the performance of KB counselors (t count = 2.494, p <0.00). The level of education has a positive and significant effect on the performance of family planning counselors (t arithmetic = 9.595, p <0.00). Work motivation and education level simultaneously have positive and significant effect on the performance of family planning counselors (F arithmetic = 13,665, p <0.00). The Contribution of Work Motivation and Education Level to the Performance of KB Extension Workers is shown by the Adjusted R Square value of 0.835 or (83.5%). The remaining 16.5% is influenced by other variables. The implication of this research is that there must be a government policy in increasing the performance of family planning counselors in the Karawang regency's Population and Family Planning Control Office (DPPKB) to improve the performance of family planning instructors through leading the process of good work motivation and increasing education levels so that the performance of family planning counselors is better.